CITEUREUP HEALTH INFORMATION PRESENTATION THROUGH INTERNET BY USING PHP AND MYSQL - Lela Subakti; Fitri Sjafrina, SKom, MMSI (Jurnal Sistem Informasi, 2006)
As the formal health institutions, health centers to hospitals began using the Internet to convey a lot of health information. By using the internet facility, patients can be directly consulted about the disease or treatment to the health center without coming directly to the location. To support the patients receive health information Citeureup, the writer had the idea of making a website that contains a variety of health information Citeureup using PHP & My SQL. Using PHP script in designing and creating dynamic websites, website maintenance is expected to become easier and the process of updating the data can be done.